2015
DOI: 10.1115/1.4030871
|View full text |Cite
|
Sign up to set email alerts
|

Response Analysis of a Nonstationary Lowering Operation for an Offshore Wind Turbine Monopile Substructure

Abstract: This study addresses numerical modeling and time-domain simulations of the lowering operation for installation of an offshore wind turbine monopile (MP) with a diameter of 5.7 m and examines the nonstationary dynamic responses of the lifting system in irregular waves. Due to the time-varying properties of the system and the resulting nonstationary dynamic responses, numerical simulation of the entire lowering process is challenging to model. For slender structures, strip theory is usually applied to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…The distributed wave forces fW,s are integrated along the MP to obtain the total wave forces and moments, FW. The added mass coefficients for different strips along the MP are chosen according to Li et al (2015c), where the excitation forces calculated using Morison's formula at different drafts were compared with those from panel method and good agreement was achieved.…”
Section: Modelling Of Hydrodynamic Forces On the Mp Morison's Formulamentioning
confidence: 99%
See 4 more Smart Citations
“…The distributed wave forces fW,s are integrated along the MP to obtain the total wave forces and moments, FW. The added mass coefficients for different strips along the MP are chosen according to Li et al (2015c), where the excitation forces calculated using Morison's formula at different drafts were compared with those from panel method and good agreement was achieved.…”
Section: Modelling Of Hydrodynamic Forces On the Mp Morison's Formulamentioning
confidence: 99%
“…Li et al (2015c) concluded that the radiation damping on the large diameter MP is of importance especially for short wave conditions in incident waves. However, the hydrodynamic interaction between the HLV and the MP was not included in Li et al (2015c), and the influences of the radiation damping of the MP in short waves for the coupled case were unknown. This study compares the effects by implementing the radiation damping on the MP for the coupled HLV-MP case.…”
Section: Morison's Formula Plus Radiation Damping For Nonstationary Pmentioning
confidence: 99%
See 3 more Smart Citations